Character Diversity of Black Rot Bacterial Strains (Xanthomonas campestris pv. campestris) on Cabbage against Mixture of Active Ingredients Azoxystrobin and Diphenoconazole - Af'idzatuttama; Nawangsih, Abdjad Asih; Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2023)
Character Diversity of Black Rot Bacterial Strains (Xanthomonas campestris pv. campestris) on Cabbage against Mixture of Active Ingredients Azoxystrobin and Diphenoconazole Xanthomonas campestris pv. campestris is a bacterium that causes black rot on cabbage. Farmers still rely on the synthetic pesticides azoxystrobin and difenoconazole to control diseases in cabbage which are feared to have an impact on the diversity of X. campestris pv. campestris. The objective of the research was to obtain genetic and phenotypic diversity data on X. campestris pv. campestris, as well as obtaining data on the resistance response of these bacterial isolates to a mixture of the active ingredients azoxystrobin and difenoconazole. The study consisted of five stages (1) sampling on land with black rot symptoms; (2) isolation of bacteria using tissue implant technique; (3) selection of isolates by testing properties of Gram, hypersensitivity, starch hydrolysis, and pathogenicity; (4) identification using specific and universal 16S rRNA primers; and (5) analysis of genotypic diversity by in silico RFLP method and phenotypic diversity by measuring EPS weight. The results of molecular characterization and identification obtained five isolates of X. campestris pv. campestris (CLT01, CDA08, SDA02, SDA22, and SDA26). The results of the analysis of genotypic diversity showed that the five isolates had genetic diversity based on the cutting of the 16S rRNA gene DNA fragment, while phenotypically indicated different Inhibition concentration (IC) values. SDA22 isolate had the highest IC50 value and different genetic diversity compared to other X. campestris pv. campestris. The use of synthetic pesticides azoxystrobin and difenoconazole continuously for a long time is feared to have an impact on pathogenic microbes such as X. campestris pv. campestris. So that other control alternatives are needed so that there is no resistance to these pathogenic microbes.